(untitled) (SCIÉNDO INGENIUM, 2021)
In this work, the levels of anticorrosive protection provided by coatings with low environmental impact on ASTM A 131-01 steel plates, exposed to the marine atmosphere of Chimbote, Peru, have been studied. Plates of dimensions 100x150x3 mm, without and with coatings of alkyd, acrylic, epoxy and siloxane type, were exposed at a distance of 250 m from the sea for three years and evaluated according to ISO 12944, ISO 8503-4, ISO 4628 standards. ISO 9223, SSPC-SP5, SSPC-PA1, SSPC-PA2, ASTM D 4541-09, SIS 05 5900, among others. Twenty-four coated plates have incisions 75 mm long and 0.5 mm wide. After three years of exposure, it was found that for the coated samples, the degree of blistering (ISO 4628-2), oxidation of the substrate (ISO 4628-3), corrosion and delamination around an incision (ISO 4628- 8), delamination distance from an incision (ISO 4628-8) were, respectively: a) alkyd coating 5 (S5), Ri5, Grade 4 and 14.35mm, b) acrylic coating 4 (S4), Ri3, Grade 2 and 1.93mm, c) epoxy coating 4 (S4), Ri4, Grade5 and 7.23mm, d) siloxane coating 2 (S2), Ri2, Grade1 and 0.25mm. The acrylic coatings based on water, epoxy and high solids Siloxane showed the best levels of anticorrosive protection.